Sub-nanosecond periodically poled lithium niobate optical parametric generator and amplifier pumped by an actively Q-switched diode-pumped Nd:YAG microlaser. (28th March 2017) - Liu, L; Wang, H Y; Ning, Y; Shen, C; Si, L; Yang, Y; Bao, Q L; Ren, G
Abstract: A sub-nanosecond seeded optical parametric generator (OPG) based on magnesium oxide-doped periodically poled lithium niobate (MgO:PPLN) crystal is presented. Pumped by an actively Q-switched diode-pumped 1 kHz, 1064 nm, Nd:YAG microlaser and seeded with a low power distributed feedback (DFB) diode continuous-wave (CW) laser, the OPG generated an output energy of 41.4 µ J and 681 ps pulse duration for the signal at 1652.4 nm, achieving a quantum conversion efficiency of 61.2% and a slope efficiency of 41.8%. Signal tuning was achieved from 1651.0 to 1652.4 nm by tuning the seed-laser current. The FWHM of the signal spectrum was approximately from 35 nm to 0.5 nm by injection seed laser. The SHG doubled the frequency of OPG signal to produce a output energy of 12 µ J with the energy conversion efficiency of 29.0% and tunanble wavelength near 826 nm.